Mood and neural responses to social rejection do not seem to be altered in resilient adolescents with a history of adversity. (May 2020) - Fritz, Jessica; Stretton, Jason; Askelund, Adrian Dahl; Schweizer, Susanne; Walsh, Nicholas D.; Elzinga, Bernet M.; Goodyer, Ian M.; Wilkinson, Paul O.; van Harmelen, Anne-Laura
Abstract: Childhood adversity (CA) increases the risk of subsequent mental health problems. Adolescent social support (from family and/or friends) reduces the risk of mental health problems after CA. However, the mechanisms of this effect remain unclear, and we speculate that they are manifested on neurodevelopmental levels. Therefore, we investigated whether family and/or friendship support at ages 14 and 17 function as intermediate variables for the relationship between CA before age 11 and affective or neural responses to social rejection feedback at age 18. We studied 55 adolescents with normative mental health at age 18 (26 with CA and therefore considered "resilient"), from a longitudinal cohort. Participants underwent a Social Feedback Task in the magnetic resonance imaging scanner. Social rejection feedback activated the dorsal anterior cingulate cortex and the left anterior insula. CA did not predict affective or neural responses to social rejection at age 18. Yet, CA predicted better friendships at age 14 and age 18, when adolescents with and without CA had comparable mood levels. Thus, adolescents with CA and normative mood levels have more adolescent friendship support and seem to have normal mood and neural responses to social rejection.